Use a medium resolution satellite imagery for population estimation in Nigeria [electronic resource] - Mustapha Aliyu, 1971- (2010)
Thesis (Sarjana Sains (Perancangan - Teknologi Maklumat)) - Universiti Teknologi Malaysia, 2010